EFEKTIVITAS AKTIVITAS PEMECAH ES DALAM MENINGKATKAN HASIL BELAJAR SISWA DALAM MATEMATIKA DI SD NEGERI 23 PAGAR ALAM - Melianda, Sendi; Julius, Julius (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the effectiveness of ice breaking in improving student learning outcomes in mathematics subjects in grade 1 of SDN 23 Pagar Alam and identify its inhibiting factors. The background of this study is the low learning outcomes of Mathematics students in grade 1 of SDN 23 Pagar Alam, which is caused by a lack of motivation and a monotonous learning atmosphere. The method used is qualitative descriptive research with data collection techniques through observation, interviews, and documentation. The population in this study is all students at SDN 23 Pagar Alam which totals 143 people. The sample was taken through the purposive sampling method, namely all 29 grade 1 students and actively applied ice breaking during classroom learning activities. The findings of this study indicate that ice breaking plays an important role in increasing students' enthusiasm, concentration, and learning achievement. The obstacles found include time constraints, inconsistencies in the type of ice breaking, diverse student characters, and limited supporting facilities and infrastructure.